Persepsi Masyarakat kota Medan Mengenai PMI yang Telah Berusia 77 Tahun - Usiono Usiono; Mila Rosdiana Sianipar; Devi Armila; Elli Annisa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Education is an important thing, including abysmal education. The Red Cross is in the city of Medan to help the people of the city of Medan. The forms of assistance are not only material but also non-material, non-material forms include blood transfusion activities, helping flood victims and evacuating them, providing public kitchens for people in need. Keywords: PMI; Birthday; community